Interspecific Competition in Birds. - Dhondt, André A. (Oxford Avian Biology., 2011)
In nature there exist three main types of biotic interactions between individuals of different species: competition, predation, and mutualism. All three exert powerful selection pressures, and all three shape communities. However, the question of how important interspecific competition in nature really is remains controversial and unresolved. This book provides a critical and exhaustive review of the topic. Although the examples are limited mostly to birds (interspecific competitionand community structure have been exhaustively studied in this animal group, and a lot of experimental data are a.